Enhanced electrocatalytic performance of functionalized carbon nanotube electrodes for oxygen reduction in proton exchange membrane fuel cells - Kannan, Ramaiyan; Bipinlal, Unni; Kurungot, Sreekumar; Pillai, Vijayamohanan K. (Physical Chemistry Chemical Physics, 2011)
Although nitrogen doped CNTs (N-CNTs) are considered as a promising alternative to platinized carbon for the oxygen reduction reaction (ORR) in polymer electrolyte membrane fuel cells (PEMFCs), the origin of the enhanced ORR activity with N-CNTs is not clear at present. Among several plausible reasons, the exposure of edge plane and creation of impurity band/surface states near the Fermi level are considered as major causes behind the catalytic activity. However, CNTs without nitrogen doping are not known to catalyze the ORR. In this work, we study the ORR activity of functionalized carbon nanotubes with different functional groups, such as sulfonic acid and phosphonic acid, in order to understand the role of surface functionalities in catalyzing the reaction. Functionalized CNTs show significantly enhanced activity towards the ORR, while CNTs without such surface functional groups do not reveal any such special ORR activity. Linear sweep voltammetry experiments with different rotation rates show diffusion controlled limiting current values for functionalized CNTs, and the `n' values derived from Koutecky-Levich plots are 3.3 and 1.7 for S-MWCNTs and P-MWCNTs, respectively. This work demonstrates the ORR activity of functionalized MWCNTs, which opens up new strategies for electrocatalyst design in PEMFCs.